Hubungan Antara Work-Familly Conflict dengan Fear Of Success Pada Guru SMK Negeri X Kota Padang - Windy Yosi Febriani; Harri Kurniawan; Rany Fitriany; Ummil Khairiyah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research aims to determine the relationship between work-family conflict and fear of success in teachers at SMK Negeri 3 Padang City. The independent variable in this research is work-family conflict and the dependent variable is fear of success. The measuring instrument used in this research is the work-family conflict and fear of success scale. The sampling technique in this research used purposive sampling, the sample in this research was 49 teachers at SMK Negeri 3 Padang. Validity and reliability testing in this research used the Cronbach Alpha technique. The results of the validity coefficient on the work-family conflict scale with the corrected item total correlation value range from 0.378 to 0.809 while the reliability coefficient is 0.927. The results of the validity coefficient on the fear of success scale with the corrected item total correlation value range from 0.317 to 0.828 while the reliability coefficient is 0.924. Based on data analysis, a correlation value of 0.774 with a significance level of 0.000 was obtained, which means the hypothesis was accepted. This shows that there is a positive and significant relationship between work-family conflict and fear of success in teachers at SMK Negeri 3 Padang. The effective contribution of the work-family conflict variable to fear of success is 60%.